Learning Model During Post Covid-19 Pandemic to Improve Early Childhood Language Development - Wantini Wantini; Suyatno Suyatno; Siti Muthia Dinni; Desfa Yusmaliana (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
Bold learning during Covid-19 causes a decrease in the quality of linguistic abilities in children because teachers cannot convey material contextually. This study aimed to analyze learning models that can be used to develop post-pandemic early childhood language skills or through face-to-face learning. This type of research is qualitative research, in which the study is carried out to understand events regarding what happened to a research subject. This phenomenological research approach seeks to let reality naturally in the research place at Nyai Ahmad Dahlan Kindergarten, Yogyakarta. The study results indicate a learning model to develop early childhood language by departing from changes in early childhood behavior in learning. Behavioral changes that lead to learning with an activity-based learning approach and multi-media-multi-method are the solutions offered in this study to improve children's language development. It contributes to the knowledge of the learning model in the post-Covid-19 pandemic toward early childhood language development.